Comparative Analysis of Rural and Urban Consumers on Milk Consumption - Kubendran, V.; Vanniarajan, T. (Indian Journal of Marketing, 2005)
India ranked second in the world after the United States of America in milk production. The per capita milk availability in India was only 200 grams per day in 1996-97 against the 220 grams requirement as recommended by the ICMR and National Institute of Nutrition. With a constant increase in disposable incomes among the strong middle-income class, the scope of marketing of milk is wider. It could be noted that the demand for milk and milk products depends on consumer’s willingness and capacity to buy. Since the consumers are not homogeneous, the consumption pattern of milk likes quantum of purchase, mode of purchase, source of purchase, brand preference etc., are changing from consumer to consumer. The socio-economic profile of the consumers namely income status, occupational position, educational level, sex, age and region are the major determinants of the consumption pattern of milk. The study of consumer behavior is inevitable to position the right product in right market at right time. The milk is not the exception to this. Hence, the present study focus on the profile of consumers, their consumption pattern in milk consumption and its correlates.